Pengaruh Kepemimpinan, Komunikasi, dan Motivasi Terhadap Kepuasan Kerja Karyawan Pada PT. Bank Perkreditan Rakyat Ronabasa Balikpapan - Simarmata, Selin Ananda; Yusuf, Tamzil; Arrywibowo , Imam (MEDIA RISET EKONOMI [MR.EKO], 2024)
Selin Ananda Simarmata (2024). The Influence of Leadership, Communication, and Motivation on Employee Job Satisfaction at PT. Bank Perkreditan Rakyat Ronabasa Balikpapan. Supervisors: Mr. Tamzil Yusuf and Mr. Imam Arrywibowo SU. The purpose of this study is to determine the influence of leadership, communication, and motivation on employee job satisfaction at PT. Bank Perkreditan Rakyat Ronabasa Balikpapan. The sampling technique used in this study is purposive sampling with a total sample of 45 employees. Data collection was conducted through the distribution of questionnaires. This research utilizes Smart-PLS to process the data. The results of this study indicate that the variables of leadership, communication, and motivation have a significant and positive effect on employee job satisfaction at PT. Bank Perkreditan Rakyat Ronabasa Balikpapan. Keywords: Leadership, Communication, Motivation, Job Satisfaction.